PHYTOCHEMICAL SCREENING AND TOXICOLOGICAL STUDY OF THE AQUEOUS EXTRACT OF STEM BARK OF MITRAGYNA INERMIS (WILD) O. KUNDZE (RUBIACEAE), A TRADITIONAL ME.DICINE PLANT. Maxime Machioud Sangare1,3*, Jean Marc Ategbo1,3, Eugene Selidji Attakpa1 , Jean Robert - Sangaré, Machioud; Ategbo, Jean-Marc; ATTAKPA, S. EUGÈNE; Klotoé, Jean Robert; Attakpa, Eugène (My University, 2017)
Background: The use of plants gained widespread as well in developing countries as in developed countries for different purposes and both as mixture or single formula. That widespread use does not guarantee their safety and efficiency. The aim of the present study is to assess the phytochemistry and subacute toxicity of Mitragynainermis, an allegatednephroprotective properties plant acclimated in Benin. Methods: By complexion and/ or precipitation reactions, the different groups of secondary metabolites in these plants were highlighted. The crude aqueous extract of M. inermis has been force-fed to rats for seven days. They were observed for toxicity signs and some blood biochemical parameters have been evaluated before and after treatment. We used Microsoft excel and Minitab 1.6 to process data. Result: Different phytochemicals were found and crude aqueous extract of M. inermis doesn’t induce toxicity signs on rats after sevenday force-feeding up to 2500 km/kg of body weight using oral route. Biochemical analysis shows a significant decrease in blood level of urea and creatinine up to 2500 km/kg of body weight. The significant increase in ALAT by D2 (1000 km/kg dose) and both in ALAT and ASAT by D3 (2500 km/kg dose) after 7 days is decreased and normalized during the observation period. Conclusion: Crude aqueous extract of M. inermis stem back is less toxic up to 2500 km/kg of body weight and should be taken during consecutively less than 7 days.
Keywords: Conclusion: Crude aqueous extract of M. inermis stem back is less; toxic up to 2500 km/kg of body weight and should be taken during; consecutively less than 7 days.